The Influence of Product Quality, Price, and Promotion on Purchasing Decisions on Mixue Products - Muhammad, Satryo Kinayungan; Kusdiyanto, Kusdiyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study was to analyze the effect of product quality, price, and promotion on purchasing decisions on Mixue products. This research method is quantitative. This study uses primary data. The data collection method used in this study was distributing questionnaires via Google Forms. The population in this study was people in Surakarta. The sampling technique in this study used purposive sampling. The sample to be used is 200 respondents. The data analysis technique in this study uses a validity test, reliability test, classical assumption test, multiple linear regression, t-test, f-test, and determination coefficient test (r2). The result of this study is that product quality has a positive but insignificant effect on purchasing decisions for Mixue products in the Surakarta Community. Price has a negative and insignificant effect on purchasing decisions for Mixue products in the Surakarta Community. Promotion has a positive and significant effect on purchasing decisions for Mixue products in the Surakarta Community.